Analysis of solubility parameters of fenbendazole in pure and mixed solvents and evaluation of thermodynamic model. (January 2020) - Yang, Zehui; Shao, Danfeng; Zhou, Guoquan
Graphical abstract: Highlights: The dissolution of fenbendazole in pure and mixed solvents. Solute-solvent interactions were analyzed. The correlation results were evaluated by statistical analysis. Abstract: In this work, the purpose is to improve the solubility of fenbendazole by co-solvent, and study the effects of solubility parameters of solvents and solute on the solubility of objective compound. The solubility of fenbendazole in pure and mixed solvents was experimentally determined and correlated by some thermodynamic models. As expected, the mole fraction solubility increased with increasing temperature, and at 298.15 K, it was ranked in the following order: 1, 4-dioxane > ethyl acetate > acetone > 1-butanol >  n -propanol > ethanol > methanol >  iso propanol > acetonitrile. Moreover, Hansen solubility parameter was applied to analyze the effect of solute-solvent intermolecular interactions on the solubility in pure solvents. Meanwhile, in order to estimate maximum solubility in the co-solvent in appropriate ratios, the solubility parameter of the mixtures was evaluated as well. In addition, based on the experimental solubility data, the correlation results of fenbendazole in pure and mixed solvents were described mathematically by using statistical analysis.